INFLUENCE OF MARKETING MANAGEMENT PRACTICUM AT KOPINMART UNPAM AGAINST STUDENT INTEREST BECOME ENTREPRENEURS - Afrida Yani; Lyandra Aisyah Margie; Habibah Habibah (Universitas Pamulang, 2019)
The purpose of this study was to determine the effect of marketing management practicum on student interest to become entrepreneurs in accounting students at UNPAM (Universitas Pamulang). This study uses a simple linear regression analysis technique. The analysis was performed using SPSS software version 24.0 The population in this study amounted to 361 active S1 Accounting Economics students who have received marketing management practicum subjects in the even semester 2018-2019, while samples taken incidentally were 118 students. The results of the research that have been done show that the marketing managemen practicum has a significant effect on student's interest to become entrepreneurs through Kopinmart UNPAM. This proves that the existence of special subjects namely marketing management practicum and the provision of facilities to Kopinmart UNPAM products can make students more confident and have a high motivation to become an entrepreneur. Keywords: Marketing management practicum, interest become entrepreneurs.